2003
DOI: 10.1039/b308418c
|View full text |Cite
|
Sign up to set email alerts
|

A single photochemical route for the formation of both copper nanoparticles and patterned nanostructured films

Abstract: Nanometer-sized copper metal can be formed by UV irradiation of ethanol bis(2,4-pentanedionate)copper(II) solutions: simple tuning of the irradiation conditions switches the process from homogeneous to heterogeneous nucleation, and promotes the formation of either colloidal powders or nanostructured films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 18 publications
(20 reference statements)
0
34
0
2
Order By: Relevance
“…Few studies have reported that copper nanoparticles exhibit excellent bactericidal properties [17][18][19][20]. Different methods have been available in the literature for the preparation of copper oxide nanoparticles, where flammable or corrosive reducing agent has been used such as titanium tetrachloride and hydrazine.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have reported that copper nanoparticles exhibit excellent bactericidal properties [17][18][19][20]. Different methods have been available in the literature for the preparation of copper oxide nanoparticles, where flammable or corrosive reducing agent has been used such as titanium tetrachloride and hydrazine.…”
Section: Introductionmentioning
confidence: 99%
“…18 Copper can also be used as an antimicrobial agent, and CuO nanoparticles have been investigated previously for enhancing antibacterial properties. [19][20][21][22] Here we report a novel gel-combustion method, controlling the size of the synthesized nanoparticles and its effect on antimicrobial characteristics. The bactericidal property of such nanoparticles depends on their size, stability, and concentration added to the growth medium, since this provides greater retention time for bacterium nanoparticles interaction.…”
Section: Introductionmentioning
confidence: 99%
“…However, copper is sensitive to air, which has resulted in there being many fewer reports on the synthesis of Cu NPs than those of other metals. During the past few decades, Cu NPs have been prepared by various approaches including gamma radiolysis [11], photochemistry [12], electrochemistry [13], and wet chemical reduction [14][15][16]. Further development of Cu NP synthesis methods has been retarded by the broad size distribution, serious agglomeration, and low stability of the nanoparticles obtained.…”
Section: Introductionmentioning
confidence: 99%